On the optimal reconstruction of the convolution of n functions according to the linear information - Babenko, V. F.; Gun’ko, M. S. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We determine the optimal linear information and the optimal method of its application to the recovery of convolution of n functions on some convex and centrally symmetric classes of 2π -periodic functions.